Dynamics of Banyumili Tourism Management Policy from the Principal-Agent Perspective - Aminullah (International Publisher, 2025)
This research aims to analyze the dynamics of the relationship between village government (principal) and the Tourism Awareness Group (Pokdarwis) as agents in managing the Banyumili Tourism Village, Kolursari, Bangil, Pasuruan. Using a qualitative case study approach, data were collected through in-depth interviews, participatory observation, document analysis, and focus group discussions. The results of the study indicate the presence of information asymmetry and potential moral hazard in the principal-agent relationship, caused by the lack of formal contracts and effective incentive mechanisms. Additionally, community participation and collaboration among stakeholders remain limited, hindering sustainable tourism management. The implications of these findings emphasize the importance of drafting clear contracts, strengthening the capacity of Pokdarwis, and enhancing community participation and multi-stakeholder collaboration. The limitation of this study lies in its focus on a single case study, so the results may not be generalizable to other contexts.